2017
DOI: 10.18632/oncotarget.16520
|View full text |Cite
|
Sign up to set email alerts
|

Patients with uterine leiomyoma exhibit a high incidence but low mortality rate for breast cancer

Abstract: The association of uterine leiomyoma with increased risk of breast cancer is controversial. Therefore, we used the National Health Insurance Research Database of Taiwan to examine breast cancer incidence and mortality among Asian patients with and without uterine leiomyoma. We compared breast cancer incidence and mortality between 22,001 newly diagnosed uterine leiomyoma patients and 85,356 individuals without uterine leiomyoma matched by age and date of diagnosis. Adjusted hazard ratios for breast cancer were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…In addition, the mortality and risk of mortality were found to be lower in women with uterine leiomyomata who developed breast cancer. 6 This is in congruence with the results of Lindegard. 18 Tseng et al published a case-control study in 2017, which revealed a significant association between uterine leiomyoma and breast cancer (adjusted OR = 1.14; 95% CI = 1.07–1.21).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the mortality and risk of mortality were found to be lower in women with uterine leiomyomata who developed breast cancer. 6 This is in congruence with the results of Lindegard. 18 Tseng et al published a case-control study in 2017, which revealed a significant association between uterine leiomyoma and breast cancer (adjusted OR = 1.14; 95% CI = 1.07–1.21).…”
Section: Discussionsupporting
confidence: 89%
“…Only a few studies have looked into disorders associated with breast cancer, along with the hormonal assays, and these studies are all medical record-based. 5 , 6 In our literature search, we could not find any studies that evaluated hormonal levels while investigating the relationship between uterine fibroids and carcinoma breast.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study used NHIRD and found a higher incidence rate of breast cancer among Taiwanese women with UM, and both diseases are strongly related by sex hormones. 17 Our study highlighted that women with UM have a higher risk of developing lung cancer.…”
Section: Discussionmentioning
confidence: 73%
“…A population-based study by Wise et al, in the USA, failed to find any association between the history of UL diagnosis and the overall incidence of breast cancer [ 5 ]. Two Asian studies based in Taiwan showed a higher incidence of breast cancer in patients with UL without increased mortality [ 6 - 7 ].…”
Section: Discussionmentioning
confidence: 99%